The structural and institutional exclusion of refugees in Australia - Losoncz, Ibolya (Berghahn Books, 2018)
Australia has been involved in the UNHCR resettlement program since 1977 and is one of the top three resettlement countries in the world. Despite considerable experience and policy and program efforts, humanitarian migrants experience lower economic and social integration than other immigrants. This chapter examines how social structures and institutional responses and practices play part to these outcomes. Drawing on data from an ethnographic study with recently settled South Sudanese refugees, and a longitudinal survey of humanitarian migrants in Australia, the chapter demonstrate that the main reason for this poor outcome is a lack of accessible pathways to refugee migrants.
Refugee Resettlement: Power, Politics and Humanitarian Governance
Keywords: Culture -- Immigrants; Social Capital -- Civic engagement; Social engagement; Culture and language; Culture; Social Capital; Immigrants; Civic engagement; Social engagement; Culture, identity and language; Culture and identity